PTBP2 - a gene with relevance for both Anorexia nervosa and body weight regulation - Zheng, Yiran; Rajcsanyi, Luisa Sophie; Herpertz-Dahlmann, Beate; Seitz, Jochen; Zwaan, Martina de; Herzog, Wolfgang; Ehrlich, Stefan; Zipfel, Stephan; Giel, Katrin; Egberts, Karin M.; Burghardt, Roland; Föcker, Manuel; et al. (Translational Psychiatry, 2022)
Genetic factors are relevant for both eating disorders and body weight regulation. A recent genome-wide association study (GWAS) for anorexia nervosa (AN) detected eight genome-wide significant chromosomal loci. One of these loci, rs10747478, was also genome-wide and significantly associated with body mass index (BMI). The nearest coding gene is the Polypyrimidine Tract Binding Protein 2 gene (PTBP2). To detect mutations in PTBP2, Sanger sequencing of the coding region was performed in 192 female patients with AN (acute or recovered) and 191 children or adolescents with (extreme) obesity. Twenty-five variants were identified. Twenty-three of these were predicted to be pathogenic or functionally relevant in at least one in silico tool. Two novel synonymous variants (p.Ala77Ala and p.Asp195Asp), one intronic SNP (rs188987764), and the intronic deletion (rs561340981) located in the highly conserved region of PTBP2 may have functional consequences. Ten of 20 genes interacting with PTBP2 were studied for their impact on body weight regulation based on either previous functional studies or GWAS hits for body weight or BMI. In a GWAS for BMI (Pulit et al. 2018), the number of genome-wide significant associations at the PTBP2 locus was different between males (60 variants) and females (two variants, one of these also significant in males). More than 65% of these 61 variants showed differences in the effect size pertaining to BMI between sexes (absolute value of Z-score >2, two-sided p < 0.05). One LD block overlapping 5′UTR and all coding regions of PTBP2 comprises 56 significant variants in males. The analysis based on sex-stratified BMI GWAS summary statistics implies that PTBP2 may have a more pronounced effect on body weight regulation in males than in females.
Gesehen am 20.07.2022